Transcutaneous Vagus Nerve Stimulation in the Treatment of Long Covid- Chronic Fatigue Syndrome - Natelson, Benjamin H; Blate, Michelle; Soto, Tiffany (Archives of Clinical and Biomedical Research, 2023)
Many patients do not recover following Covid infection. The resulting illness is called Long Covid. Because there is no agreed upon treatment for this ailment, we decided to do an open label pilot study using non-invasive, transcutaneous stimulation of the auricular branch of the vagus nerve. Inclusion criteria required the patient to fulfill criteria for having chronic fatigue syndrome. Fifteen patients provided evaluable data. Eight of these fulfilled our requirements for treatment success. Since our criterion for a successful study was that at least a third of patients had to show a positive response to treatment, this was a successful pilot that warrants a follow up study that is appropriately sham controlled.